Comparing fluorescence-based cell-free assays for the assessment of antioxidative capacity of high-density lipoproteins. - Tsunoda, Fumiyoshi.; Lamon-Fava, Stefania.; Horvath, Katalin V.; Schaefer, Ernst J.; Asztalos, Bela F. (2016)
Background: Population studies have shown an inverse association between high-density lipoprotein (HDL) cholesterol levels and risk of coronary heart disease (CHD). HDL has different functions, including the ability to protect biological molecules from oxidation. Our aim was to evaluate the performance of two fluorescence-based assays in assessing the antioxidative capacity of HDL.; Keywords: High density lipoprotein, Oxidation, Coronary heart disease, Fluorescence assay.; Springer Open.